Efektifitas Senam Hipertensi terhadap Tekanan Darah Lansia di Puskesmas Rawat Inap Muaro Kumpeh - Dwi Yunita Rahmadhani; Nel Efni; Yuliana Yuliana; Marnila Yesni (Jurnal Akademika Baiturrahim Jambi, 2023)
Elderly (elderly), is a process of the final stages of a human life. One of the problems that often occurs in the elderly is hypertension. Hypertension is a condition where the elderly have blood pressure above 14/90 mmHg. One way that can be done to lower blood pressure is hypertension exercise. In Muaro Jambi Regency, based on data from the Muaro Jambi District health office, the health center with the highest number of elderly people with hypertension was the Muara Kumpeh inpatient health center with a total of 2190 cases of hypertension. The purpose of this study was to determine the effect of hypertension exercise on elderly blood pressure at the Muara Kumpeh Inpatient Health Center in 2021. This research is a quantitative study using the pre-experimental method with one group pre-test post-test design. This research was conducted in September 2021 – August 2022 at the Muara Kumpeh Inpatient Health Center. The total population is 2190 people with a sample of 10 people taken by purposive sampling technique. Data collection was done by observing blood pressure before and after the intervention, which was carried out once a week for three weeks. Blood pressure data were analyzed using paired sample t-test with α < 0.05. The results of research conducted at the Muaro Kumpeh Inpatient Health Center found that hypertension exercise had an effect on elderly blood pressure (p-value = 0.000). Where the average systolic blood pressure decreased by 40 mmHg and the average diastolic blood pressure decreased by 20 mmHg. Suggestions that elderly hypertension exercise can be an alternative exercise that can be given to the elderly to lower blood pressure and for further research can add insight to researchers on the relationship between the level of influence of hypertension exercise on elderly blood pressure.